The Implementation of the PCK-Based Electricity and Magnetism Textbook on Student Learning Outcomes - Boisandi, Boisandi; Alsagaf, Sy. Lukman Hakim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This study aims to investigate the implementation of electric-magnetic textbooks based on Pedagogical Content Knowledge (PCK) on learning achievement in the physics education IKIP PGRI Pontianak. The problem is that there needs to be more consistency between the mastery of theory and practice of students, especially in practice in the laboratory. Students need help to implement the theory they have learned into practice. The electric magnetic textbook has advantages: the pedagogic structure and content balance theory with practice. It has been adapted to the learning achievement of the magnetic electricity course in the physics education study program of IKIP PGRI Pontianak. The sequential embedded mixed-method design was used in this study to extract information from the research subject. The research was conducted at the Physics Education IKIP PGRI Pontianak. The object of this research is the student of Physics Education IKIP PGRI Pontianak Semester VI Academic Year 2021/2022. The data collection technique used in this study is an indirect communication technique with research instruments such as pretest-posttest questions and response questionnaires and interviews. The first qualitative stage obtained an average response of all aspects of 79% with high criteria. Learning effectivity is obtained based on the average normalized gain <g> of 0.57 with medium criteria. There is an increase in student learning achievement obtained from the response questionnaire after treatment by 81%; the category is very high. The interview showed the consistency of increasing student learning achievement on magnetic electricity.